Preparticipation physical examination using a box drop vertical jump test in young athletes - Hewett, T. E.; Myer, G. D.; Ford, K. R.; Slauterbeck, J. R. (Clinical Journal of Sport Medicine, 2006)
Objective: Neuromuscular performance increases rapidly in males throughout pubertal development, whereas no similar neuromuscular spurt occurs in females. This fact may underlie neuromuscular imbalances related to increased risk of injury in females. The hypothesis: female athletes would demonstrate mismatched landing force to power production compared with males.